Flow-Control Systems Proof of Concept for Snowmelt Runoff at McMurdo Station, Antarctica - Affleck,Rosa T; Tischbein,Bruce; Arbogast,Jude (2017)
The snowmelt runoff during the austral summer at McMurdo Station is diurnally and seasonally variable. The variability is caused by a dynamic process in which the flow fluctuates daily and seasonally in response to solar and temperature input, melting the snow and glacier ice in the watershed. The current state of drainage at McMurdo Station has operational challenges and environmental impact when incidents of extreme flow occur. A surge of massive amounts of runoff downstream overwhelms both the drainage-system capacity and operational personnel and mobilizes sediments and transports potential and known contaminants downstream. The purpose of this project was to demonstrate the feasibility and use of flow-control systems (including wooden and rock weirs) to attenuate flow in drainage channels and digging settling basins to contain snowmelt. When runoff was light to moderate, the weirs performed well, collecting sediments and attenuating the diurnal flows in the channels. However, the weirs became nonfunctional under high and surge flows. Experimental settling basins were constructed to determine whether they will retain the snowmelt and whether their berm and spillway will hold up and attenuate the flow. Moreover, this report highlights best management practices and lessons learned for sustained elimination of erosion and for reduced drainage-system maintenance.